Implementasi Program Gerakan Literasi Madrasah (Gelem) Di Ma At-Taufiqiyah Bluto Sumenep - Imam Basofi; Moh. Marsuki (AL -ALLAM, 2022)
Madrasah literacy is an effort to make madrasas a literate educational organization. The Madrasah Literacy Movement (GELEM) needs to be implemented because it has a function as a driver in growing character, the ability to process information, improve thinking and analysis skills.This study aims to: 1) Describe the implementation of the Madrasah Literacy Movement Program. 2) Describe the supporting and inhibiting factors for the Implementation of the Madrasah Literacy Movement Programe.This study uses a qualitative descriptive approach, namely research that seeks to describe and interpret objects as they are. The key instrument is the researcherhimself, and the data collection techniques used are observation, interviews and documentation. The research location is in MA At-Taufiqiyah Bluto Sumenep. The data were analyzed by reducing the data and presenting the data, and drawing conclusions, then by testing the validity of the data from the research results, an extension of the research was carried out, increasing persistence and also triangulation.The results showed that, 1) The implementation of the Madrasah Literacy Movement Programe at MA Attaufiqiyah were: a) the basis of activities, b) the steps for literacy activities, 2) the supporting and inhibiting factors for the implementation of the Madrasah Literacy Movement Programe: a) Supporting factors for the availability of facilities that became supporting the application of student literacy culture, b) The inhibiting factor is that it takes longer because there is still little time, then students still do not understand the books they read so they still need guidance from the teacher.